The effect of the organizational climate dimensions in the organizational silence A Survey on a sample of views of the administrative employees at the university of Zakho - Yousef, Mehvan S. (Humanities Journal of University of Zakho, 2016)
This research aims to investigate the effect of organizational climate dimensions (organizational structure, leadership style, participation in decision taking, and work procedures) in the organizational silence, and the University of Zakho was selected to perform the practical field of the research, the sample of research included (100) from the managerial employee, a form of questionnaire was designed with the help of a group of experts for data collection, the data were analyzed using several statistical tools. The most important of research conclusions are that there is a significant correlation and effect between organizational climate dimensions and organizational silence in University of Zakho. The research found a set of proposals the most important of them was: it is nessecary for the Managing Directors hold regular meetings with the employee staff allows them to dialogue without restrictions to get know their views and suggestions on how to build an appropriate regulatory climate for the exchange of information and knowledge and talk about the organizational problems they face and the diagnosis of the factors that caused their sense of silence organizational and address to those factors .